2015
DOI: 10.3109/17435390.2015.1073811
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and developmental toxicity of carbon-based nanomaterials: A literature review

Abstract: We summarized the findings of reproductive and developmental toxicity studies on carbon-based nanomaterials (CNMs). Placental transfer of fullerenes in rats and single-walled (SW) and multi-walled (MW) CNTs in mice was shown after intravenous injection. SWCNTs appeared to be embryolethal and teratogenic in mice when given by intravenous injection and induced death and growth retardation in chicken embryos. In mice-administered MWCNTs, fetal malformations after intravenous and intraperitoneal injections and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(73 citation statements)
references
References 102 publications
1
70
1
1
Order By: Relevance
“…A recent review suggested that the placenta does not provide a tight barrier against the transfer of nanoparticles to foetuses, specifically against the distribution of carbonaceous nanoparticles to and in the foetus [42]. It was suggested that rGO and gold particles (diameter of 13 nm) are barely present or are absent in the placenta and foetus in late gestation after intravenous injection [44, 68].…”
Section: Toxicity Of Gfns (In Vivo and In Vitro)mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review suggested that the placenta does not provide a tight barrier against the transfer of nanoparticles to foetuses, specifically against the distribution of carbonaceous nanoparticles to and in the foetus [42]. It was suggested that rGO and gold particles (diameter of 13 nm) are barely present or are absent in the placenta and foetus in late gestation after intravenous injection [44, 68].…”
Section: Toxicity Of Gfns (In Vivo and In Vitro)mentioning
confidence: 99%
“…For example, some graphene nanomaterials aerosols can be inhaled and substantial deposition in the respiratory tract, and they can easily penetrate through the tracheobronchial airways and then transit down to the lower lung airways, resulting in the subsequent formation of granulomas, lung fibrosis and adverse health effects to exposed persons [2, 29]. Several reviews have outlined the unique properties [35, 36] and summarized the latest potential biological applications of GFNs for drug delivery, gene delivery, biosensors, tissue engineering, and neurosurgery [37–39]; assessed the biocompatibility of GFNs in cells (bacterial, mammalian and plant) [7, 40, 41] and animals (mice and zebrafish) [42]; collected information on the influence of GFNs in the soil and water environments [43]. Although these reviews discussed the related safety profiles and nanotoxicology of GFNs, the specific conclusions and detailed mechanisms of toxicity were insufficient, and the mechanisms of toxicity were not summarized completely.…”
Section: Introductionmentioning
confidence: 99%
“…It follows from the present knowledge of the relationship between NP and the human body (2,3,5,8,9,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) that:…”
Section: Fig 1 Comparison Of Micro-objects With Nano-objects Editementioning
confidence: 99%
“…Developmental effects were seen for other MWCNT types than those assessed in this study at concentrations causing maternal toxicity and when using non-physiological routes of exposure (IV injection, intraperitoneal injection, intratracheal instillation) (Hougaard et al, 2013, Ema et al, 2016). Chronic inflammation is considered to interfere with reproductive parameters.…”
Section: Resultsmentioning
confidence: 70%